Assessing the quality and effectiveness of isiXhosa translations in public health communication materials to advance health equity in Nelson Mandela Bay - Sinawo Siphosethu Lukubeni (Discover Public Health, 2026)
Abstract Language is a critical determinant of health equity in South Africa’s multilingual healthcare system. Despite constitutional mandates to communicate in indigenous languages such as isiXhosa, many public health materials remain inadequately translated, compromising access to essential health information. This study assesses the quality and effectiveness of isiXhosa translations of two key public health artefacts, the Patients’ Rights Charter and an Immunisation Poster, found in Nelson Mandela Bay clinics. The aim is to evaluate whether these translations support or hinder public health objectives such as informed consent, patient empowerment, and equitable access to care. Using a qualitative case study design, the English and isiXhosa versions of both artefacts were analysed using Skopos Theory, Equivalence Theory, and the Social Accountability Framework. Evaluation criteria included grammatical accuracy, cultural relevance, and functional clarity. No primary participants were involved. Findings reveal significant variation in translation quality. The Patients’ Rights Charter contained literal translations, grammatical errors, and transliterations that may impede patient understanding. In contrast, the Immunisation Poster employed culturally adapted, idiomatic language that enhanced clarity and engagement. These differences have direct implications for health literacy, communication equity, and trust in public health messaging. The study highlights persistent gaps in how language policy is reflected and operationalised in translated public health materials. It recommends institutional investment in culturally competent translation practices, participatory review processes, and strengthened policy enforcement mechanisms. Strengthening language access in public health communication is essential for reducing health disparities and advancing universal health coverage in South Africa.